Application of array comparative genomic hybridization in clinical diagnostics of intellectual disability/developmental delay in children - Uppal, Komal; Rana, Lakshay; Polipalli, Sunil Kumar; Kumar, Somesh; Jindal, Ankur; Kapoor, Seema (International Journal of Contemporary Pediatrics, 2023)
Background: This study was designed to analyze and evaluate the potential pathogenic genomic imbalance in children with unexplained intellectual disability (ID) and/or developmental delay (DD) and its association with phenotypes, and to investigate the value of array-based comparative genomic hybridization (array-CGH). Methods: A total of 72 Children with ID/DD were evaluated by array-CGH for detection of genomic copy number variations (CNVs). Results: The results of the array-CGH revealed that 10(14%) of the 72 patients had pathogenic CNVs, in that six cases had pathogenic CNV in a single chromosome, 2 cases had multiple microdeletions and 2 cases had combined microdeletion and microduplication, 2 cases had pathogenic CNVs in chromosome 1p36 and Xq28 region. One case had variation of unknown significance in chromosome region 15q11.2. Large bands of copy neutral loss of heterozygosity were detected in 2 cases comprising more than 10% of genome. Conclusions: Array-CGH being a high-throughput and rapid tool, allows for the etiological diagnosis in some of the children with unexplained ID/DD.